2022
DOI: 10.31234/osf.io/q64zp
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Where you come from matters: Cultural differences in mobility perceptions and status judgments

Abstract: The present research investigated how culture affects status-related judgments. We examined two Western cultures that, because of their differing socio-ecological histories, were predicted to vary in how information about a person’s familial social class background would affect judgments about this person’s status in a variety of domains. Study 1 demonstrated that, compared to American participants, French participants perceived a lesser likelihood of career success for a target described with a lower (versus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…For example, age is a very important component of social ranking in East Asian cultural contexts (Sung, 2001), and recent research found that business and political leaders were significantly older in East Asian compared to Western cultural contexts (Vaughan-Johnston et al, 2021). Moreover, individuals from the French cultural context acknowledged that familial class background was a more important basis for occupying high rank compared to individuals from an American cultural context (Gobel & Kim, 2023). Consistent with these findings, individuals from Mediterranean European cultural contexts, such as Italy or France, compared to individuals from the American cultural context, also reported perceiving less inter generational mobility (Alesina et al, 2018).…”
Section: Future Research Questionsmentioning
confidence: 99%
“…For example, age is a very important component of social ranking in East Asian cultural contexts (Sung, 2001), and recent research found that business and political leaders were significantly older in East Asian compared to Western cultural contexts (Vaughan-Johnston et al, 2021). Moreover, individuals from the French cultural context acknowledged that familial class background was a more important basis for occupying high rank compared to individuals from an American cultural context (Gobel & Kim, 2023). Consistent with these findings, individuals from Mediterranean European cultural contexts, such as Italy or France, compared to individuals from the American cultural context, also reported perceiving less inter generational mobility (Alesina et al, 2018).…”
Section: Future Research Questionsmentioning
confidence: 99%